The Application of a Career Guidance-Based Genogram Technique and Its Effect on High School Students' Career Maturity - Kaffah, Muhammad Silmi; Hikmah, Muh. Syawal; Agussalim, Agussalim (IKIP Siliwangi, 2025)
This study examines the genogram technique's implementation and effectiveness in enhancing students' career maturity at SMAN 2 Jeneponto. The research employed a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The study population consisted of 30 eleventh-grade science students, with a sample of 20 students divided into two groups: 10 in the experimental group and 10 in the control group. Data were collected through questionnaires and observations and then analyzed using descriptive statistics and a t-test. The results showed that implementing the genogram technique over five sessions significantly improved students' career maturity. Students in the experimental group demonstrated high levels of participation and greater improvements in career maturity scores compared to those in the control group. In conclusion, the genogram technique proved effective in helping students understand their career choices. These findings have important implications for school guidance and counseling practices, particularly in career guidance services. The use of genograms is effective in helping students explore their family's career background and develop greater self-awareness about their career decisions.